(SCp)Rhodium‐Catalyzed Asymmetric Satoh–Miura Reaction for Building‐up Axial Chirality: Counteranion‐Directed Switching of Reaction Pathways. (8th December 2022) - Zhang, Wen‐Wen; Wang, Qiang; Zhang, Su‐Zhen; Zheng, Chao; You, Shu‐Li
Abstract: Satoh–Miura reaction is an important method for extending π‐systems by forging multi‐substituted benzene rings via double aryl C−H activation and annulation with alkynes. However, the development of highly enantioselective Satoh–Miura reaction remains rather challenging. Herein, we report an asymmetric Satoh–Miura reaction between 1‐aryl benzo[ h ]isoquinolines and internal alkynes enabled by a SCpRh‐catalyst. Judiciously choosing the counteranion of the Rh‐catalyst is crucial for the desired reactivity over the competitive formation of azoniahelicenes. Detailed mechanistic studies support the proposal of counteranion‐directed switching of reaction pathways in Rh‐catalyzed asymmetric C−H activation. Abstract : A highly enantioselective Satoh–Miura reaction enabled by a chiral tri‐substituted SCpRh(III)‐catalyst is described. The desired axially chiral products can be afforded in moderate to excellent yields (up to 85 %) and excellent enantioselectivity (up to 96 % ee). Meanwhile, DFT calculations provide rationales behind this unique phenomenon of counteranion‐directed switching of the pathways in C−H activation reactions.